Tax Compliance Decision Analysis: Audit Strategy, Audit Rate, Perceived Probability of Audit, and Taxpayer Ethics - Asnawi, Meinarni (Information Management and Business Review, 2016)
This study aims to provide empirical evidence that audit strategy, audit rate, perceived probability of audit and taxpayer ethics have impact on tax compliance. This Research employs the experimental laboratory method with multiple treatment design to refer behavioral change in tax compliance decision. 156 voluntary student participants were recruited from three major; accounting, management, and economics major. The participants grouped into random and fixed group adaptable with audit strategy treatment. Random selection is used to establish participant to each group. Audit rate treatment was classified in four audit level; uninformed audit rate, 10%, 20%, and finally 30%. Perceived probability of audit treatment; subjects determine the percentage of perceived audit. Furthermore taxpayer ethics treatment uses tax ethics film. The results provide empirical evidence that in the random group, strategy random audit, audit rate, perceived probability of audit and taxpayer ethics have significant relationship with tax compliance decision. Conversely, fixed group disprove that audit fixed strategy insignificantly with tax compliance decisions. Audit fixed strategy and audit rate have indirect relationship to tax compliance decision by perceived probability of audit. These results from both of group may suggest that taxpayers will increase the tax compliance decision when his possibility to be audited is high. Taxpayer ethics has significant impact on tax compliance decision at all audit level. Taxpayer ethics plays an important role of increased tax compliance decision. This study has implication for judgment theory to consider taxpayer ethics.